The Effect of Profitability and Financial Risk on Earning Management of Mobile Telecommunication Operators That Registered in Indonesia Stock Exchange Period 2015 - 2018 - Eneng Dilah Dalilatur Rahmah; Yusuf Iskandar (Nusantara Science and Technology Proceedings, 2020)
The purpose of this research is to analyze the partial and simultaneous effect of profitability and financial risk on earnings management. The sampling method of this research is purposive sampling with the 3 largest Indonesian provider companies that registered on Indonesia Stock Exchange (IDX) in 2015 – 2018 as the sample. This research used secondary data from IDX with multiple linear regression as the analysis technique. The result of this research indicates that partially profitability and financial risk hurts earnings management. While simultaneously profitability and financial risk showed a positive effect on earnings management.